Stylistic analysis of Rola ou enrola? (a.k.a. conveyor belt of love): a narrative that unfolds in the program Eliana (SBT) (Comunicação & Inovação, 2018)
TV shows are macronarratives in which inhabit several diegesis, each one with their specific plots and characters; they are called segments. The dominical show Eliana (2009-) fits this profile, comprehending, among a sum of microuniverses made of (in)finite expressive resources, the weekly Rola ou enrola? (known in English as Conveyor Belt of Love). In order to discuss the stylistic effects responsible for maintaining the viewer's interest in a dating segment about to complete a quadrennium on air, it was questioned what is peculiar, in a cultural and communicational sense, about the object in evidence.
Keywords: Audiovisual. Television. Media narratives. Stylistics. SBT.